2020
DOI: 10.1002/jmri.27353
|View full text |Cite
|
Sign up to set email alerts
|

Altered Dynamic Functional Connectivity in Patients With Mitochondrial Encephalomyopathy With Lactic Acidosis and Stroke‐Like Episodes (MELAS) at Acute and Chronic Stages: Shared and Specific Brain Connectivity Abnormalities

Abstract: BackgroundMitochondrial encephalomyopathy with lactic acidosis and stroke‐like episodes (MELAS) is a rare maternally inherited genetic disease; however, little is known about its underlying brain basis. Furthermore, the dynamic functional connectivity (dFC) of brain networks in MELAS has not been explored.PurposeTo investigate the abnormalities of dFC in patients with MELAS at the acute and chronic stages, and to determine the possible relations between dynamic connectivity alterations and volumes of stroke‐li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Wang et al ( 51 ) reported that MELAS patients, particularly those at the acute stage, exhibited topological reorganization of the whole-brain functional network based on resting-state fMRI. They also found that MELAS patients spent more time in a state with weaker connectivity and less time in states with stronger connectivity, and patients at the acute stage exhibited that global efficiency was markedly increased while local efficiency was decreased, compared to the controls and the patients at the chronic period ( 52 ). Additionally, Rodan et al ( 53 ) demonstrated that MELAS patients' fMRI activation in response to visual cortex stimulus was significantly increased in primary visual striate cortex V1 and extrastriate regions V2 to V5 after L-arginine treatment with task fMRI.…”
Section: Funtional Mri Findingsmentioning
confidence: 98%
“…Wang et al ( 51 ) reported that MELAS patients, particularly those at the acute stage, exhibited topological reorganization of the whole-brain functional network based on resting-state fMRI. They also found that MELAS patients spent more time in a state with weaker connectivity and less time in states with stronger connectivity, and patients at the acute stage exhibited that global efficiency was markedly increased while local efficiency was decreased, compared to the controls and the patients at the chronic period ( 52 ). Additionally, Rodan et al ( 53 ) demonstrated that MELAS patients' fMRI activation in response to visual cortex stimulus was significantly increased in primary visual striate cortex V1 and extrastriate regions V2 to V5 after L-arginine treatment with task fMRI.…”
Section: Funtional Mri Findingsmentioning
confidence: 98%
“…To decompose the preprocessed rs-fMRI data into different independent components (ICs), a spatial group ICA was performed using the Group ICA of fMRI Toolbox (GIFT, version 4.0b) 2 ( Calhoun et al, 2001 ). Although some studies selected a high-order ICA approach to obtain cortical and subcortical functional parcellations ( Kim et al, 2017 ; Fiorenzato et al, 2019 ; Wang et al, 2021 ), we applied a low-order model, given the fact that the ICs obtained from the lower-order model were more consistent with previous anatomical and functional segmentations ( Calhoun et al, 2008 ; Smith et al, 2009 ; Shi et al, 2018 ). Group ICA included the following steps: first, a two-step principal component analysis (subject-specific and group level) was used to decompose the data into 23 ICs.…”
Section: Methodsmentioning
confidence: 99%
“…When the mental activity is unconstrained, dynamics are potentially even more prominent under the resting state. Evidences suggested that dynamic functional connectivity (DFC) supply us new information about abnormal FC on the brain of patients with various diseases (Demirtas et al, 2016;Guo et al, 2018;Wang et al, 2020;Chen et al, 2020a,b). However, the abnormal DFC and the neural activity change after acupuncture treatment were unclear in tinnitus patients.…”
Section: Introductionmentioning
confidence: 99%